Potential Benefits and Downsides of External Healthcare Performance Evaluation Systems: Real-Life Perspectives on Iranian Hospital Evaluation and Accreditation Program - Ebrahim Jaafaripooyan (Kerman University of Medical Sciences, 2014)
Background Performance evaluation is essential to quality improvement in healthcare. The current study has identified the potential pros and cons of external healthcare evaluation programs, utilizing them subsequently to look into the merits of a similar case in a developing country. Methods A mixed method study employing both qualitative and quantitative data collection and analysis techniques was adopted to achieve the study end. Subject Matter Experts (SMEs) and professionals were approached for two-stage process of data collection. Results Potential advantages included greater attractiveness of high accreditation rank healthcare organizations to their customers/purchasers and boosted morale of their personnel. Downsides, as such, comprised the programs' over-reliance on value judgment of surveyors, routinization and incurring undue cost on the organizations. In addition, the improved, standardized care processes as well as the judgmental nature of program survey were associated, as pros and cons, to the program investigated by the professionals. Conclusion Besides rendering a tentative assessment of Iranian hospital evaluation program, the study provides those running external performance evaluations with a lens to scrutinize the virtues of their own evaluation systems through identifying the potential advantages and drawbacks of such programs. Moreover, the approach followed could be utilized for performance assessment of similar evaluation programs.